ObReco-2: Two-step validation of a tool to assess memory deficits using 360° videos - Bruni, Francesca; Mancuso, Valentina; Stramba-Badiale, Chiara; Greci, Luca; Cavallo, Marco; Borghesi, Francesca; Riva, Giuseppe; Cipresso, Pietro; Stramba-Badiale, Marco; Pedroli, Elisa (Frontiers in Aging Neuroscience, 2022)
Traditional neuropsychological evaluations are usually carried out using psychometric paper and pencil tests. Nevertheless, there is a continuous discussion concerning their efficacy to capture life-like abilities. The introduction of new technologies, such as Virtual Reality (VR) and 360° spherical photos and videos, has improved the ecological validity of the neuropsychological assessment. The possibility of simulating realistic environments and situations allows clinicians to evaluate patients in realistic activities. Moreover, 360° photos and videos seem to provide higher levels of graphical realism and technical user-friendliness compared to standard VR, regardless of their limitations in terms of interactivity. We developed a novel 360° tool, ObReco-2, for the assessment of visual memory which simulates a daily situation in a virtual house. More precisely, patients are asked to memorize some objects that need to be moved for a relocation. After this phase, they are asked to recall them after 15 minutes and later on to recognize them in the same environment. Here we present a first study about the usability of ObReco-2, and a second one exploring its clinical efficacy and updated usability data. We focused on Free Recall and Recognition scores, comparing the performances obtained by the participants in the standard and the 360° test. The preliminary results support the use of 360° technology for enhancing the ecological value of standard memory assessment tests.